DAMPAK PERUBAHAN IKLIM TERHADAP PERMUKIMAN PESISIR DI KELURAHAN DEMAAN KABUPATEN JEPARA - S Sunarti; Nur Khasanah Apriliasari (Diponegoro University, 2015)
Increasing of the climate change influences the community life and natural resources in the coastal areas. Demaan Sub-district, Jepara Regency as the coastal area directly have an impact of climate change such as a tidal flood. This condition makes the community doing adaptation toward to their environment. The research objective is identifying of climate change toward to the settlement in Demaan coastal area. The research approach used mix method of concurrent by combining data of quantitative and qualitative. A quantitative method used to find out the respondents characteristic from the questionnaire result by descriptive statistical analysis. A qualitative method used to explain the problem and study findings of climate change impact and adaptation conducted by the community. The climate change impact in Demaan coastal area which increased in temperature, tide timetable, tidal flood, brine, sedimentation, dryness, and strong wind. The community conducted adaptation by upgrading on floor, wall, and rooftop. Upgrading of infrastructures by rising of road dimension, improving drainage system, developing public sanitation, and improving waste disposal manage by a provision of landfill close to Apung Market. The Government recommendation should develop related regulation and monitoring of the settlement development in the vulnerable areas of disasters.